African People's History Month Poetry Jam moved to Feb. 27 - Uribes, Tom::::::::: (2013)
The African People's History Month Poetry Jam at Fresno State, originally scheduled for tonight, has been moved to 7-10 p.m., Wednesday, Feb. 27.